A Multicriteria Dm Framework in the Eco-Management of Operations: A Case of Organic Waste Reuse - Oddershede-Herrera, A (Elsevier B.V., 2023)
This article presents a case study for decision-making regarding the reuse of organic waste. It introduces a framework for eco-management operations using a multi-criteria approach based on the perspective of organizational stakeholders. Applying the Analytical Hierarchical Process (AHP) it was possible to prioritize options in an environmentally sustainable and economically viable way. The framework integrates several criteria, such as environmental impact, economic viability, social acceptability and regulatory compliance, to provide a comprehensive and robust assessment of alternatives. A decision model is developed to identify the main concern attributes for determining the most suitable process for organic waste treatment. Empirical data has been collected from a central supplier located in the metropolitan region, in Chile. This supplier site contributes as an externality approximately 50% of the waste of the neighborhood where it is located and approximately 10% of the operational costs for the organization. The procedure is followed according to the methodological approach of the study including the experience and perspectives of the actors of the organization. The case study results indicate the efficacy and practicality of the multi-criteria framework in supporting eco-management decision-making processes. © 2023 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the scientific committee of the Tenth International Conference on Information Technology and Quantitative Management.